(Ideological Opinions for Al-Imaam Sahl bin Abd-Allah Altastory in the faith : A Collection and Study) - Khadir, Mohammed; Hamad , Khayal (Islamic Sciences Journal, 2023)
The present study is divided into (Ideological opinions for Al-Imaam Sahl bin Abd-Allah Altostery in the faith – Collection and Study) into two study parts that are preceded by (Altostery’s sayings about the faith as in: working, intention, Sunna as well as increasing and decreasing of the faith ). The researcher has divided this research into three demands. In first demand the paper posited the definition of faith in language and in idiom while in second demand shows Altostery’s saies about the faith as in, working, intention and Sunna. In third demand the increasing and decreasing of faith as Altostery says. The second research (The relationship between the faith and the Islam as Altostery says) that was divided into tree demand. In first demand the paper showed endorsement in Islam and certainly in faith as Altostery says, In the second demand Altostery includes identifying between the faith and Islam when they meet. The third demand is about Altostery sayings about the faith. the study ends with conclusion that has contained all important results of this study then followed with references.